Stanisław Dutkiewicz – a gift realised by disease - Welcz, Henryk; Pawęzka, Justyna (Current Problems of Psychiatry, 2015)
Stanisław Dutkiewicz lived from 1923 to 2003. He was a lawyer, a famous painter and a graphic artist. He lived in Grodzisk Mazowiecki. In the early years of his life he was diagnosed as having the bipolar affective disorder, and he was treated in the Psychiatric Hospital in Tworki. Such was his treatment as a patient that, for many years, he was a member of the Association of the Friends of Tworki – the “Amici di Tworki”. His pictures can be seen in exhibitions of fine art in Poland, Europe and the USA. Moreover, his works were seen as being highly appreciated in many publications devoted to art brut, not least, those of the Association of the Friends of Tworki.